Estimating the potential fisheries production of three offshore reefs in the West Philippine Sea, Philippines - Arceo, Hazel O.; Mamauag, Samuel S.; Luciano, Rhea Mae A.; Heyres, Lovely Joy D.; Cabasan, Joey P.; Aliño, Porfirio M. (2020)
Evaluating reef fisheries potential is crucial in understanding the benefits derived from coral reefs. In this study, fisheries production of three offshore reefs in the West Philippine Sea was characterized using both fishery-dependent and fishery-independent approaches. Experimental fishing was done using speargun and multiple hook-and-line in Pagasa Island and Sabina Shoal, Kalayaan Island Group (KIG) while interviews to assess fisheries production for the Scarborough Shoal were conducted in Masinloc, Zambales. Catch composition, total catch, and catch rates were obtained. Catch composition differed among gears although it was commonly dominated by Acanthuridae, Balistidae, Lethrinidae, and Scombridae. The catch rate was lowest for hook-and-line across all sites. Using varying levels of fishing days per year, mean catch rates ranged from 0.25?1.53 mt/fisher/yr for hook-and-line and 1.26?3.80 mt/fisher/yr for spearfishing. Estimated yields ranged from 2?31 mt/km2/yr. The potential annual yield for the three reefs was 1,053?2,733 mt/yr. When extrapolated, the KIG reefs can potentially produce around 61,557?90,850 mt/yr, or 3?5% of the total marine capture fisheries output. Interview results further revealed that the dominant gear type in Scarborough changed from speargun in the past to gillnets at present. This could be attributed to an observed shift in fishing grounds when access to the reefs became more restricted. The study shows that fisheries production in the three offshore reefs is still high compared with other areas in the country. However, these reefs have remained exposed to various anthropogenic threats, which could lead to significant fisheries losses if they remain unmanaged. Especially in offshore reefs where benchmarks are lacking, information on fisheries productivity should be compiled if it were to be sustained. (Author's abstract)
Includes bibliographical references (pages 641-642)
Keywords: Biology; Coral reef; Fisheries; Kalayaan island group; Offshore; Scarboroug -- West Philippine sea